2002
DOI: 10.1097/00006534-200212000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Wet Wound Healing

Abstract: Wound treatment in a flexible transparent chamber attached to the perimeter of the wound and containing a liquid has been extensively tested in preclinical experiments in pigs and found to offer several advantages. It protects the wound; the liquid medium or saline in the chamber provides in vivo tissue culture-like conditions; and antibiotics, analgesics, and various molecules can be delivered to the wound through the chamber. The wound chamber causes no injury to the wound itself or to the surrounding intact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 16 publications
0
39
1
1
Order By: Relevance
“…In both pre-clinical and clinical studies, the hyper-hydrated wound environment proved to be safe for the treatment of a number of wounds. Wound healing under these hyper-hydrated conditions progressed in a similar manner to those where moist conditions were used 30,52 -the wounds showed less tissue necrosis, faster healing rates and a better quality of healing, compared with dry wounds.…”
Section: Hyper-hydration Of Tissue and Healingmentioning
confidence: 79%
See 2 more Smart Citations
“…In both pre-clinical and clinical studies, the hyper-hydrated wound environment proved to be safe for the treatment of a number of wounds. Wound healing under these hyper-hydrated conditions progressed in a similar manner to those where moist conditions were used 30,52 -the wounds showed less tissue necrosis, faster healing rates and a better quality of healing, compared with dry wounds.…”
Section: Hyper-hydration Of Tissue and Healingmentioning
confidence: 79%
“…49 Irrespective of the cause, the presence of maceration has led to the assumption that a surfeit of moisture will inevitably lead to sustained tissue damage. However, a number of studies have indicated that a wound that is overly hydrated may not result in tissue damage, [50][51][52] and rather suggest that a wound bathed in a hyper-hydrated environment may benefit from the advantages of moist wound healing. 30 This is demonstrated in Figure 10.…”
Section: Hyper-hydration Of Tissue and Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend is challenging to explain considering previous literature suggesting moist wound environment with occlusive dressings improves chronic wound healing by stimulating granulation tissue, and inducing autolytic debridement. 2,3,22,23 However, the possibility of ulcer infection is the most significant disadvantage of moist wound healing, along with risk of inducing an exudative phase in an otherwise dry ulcer. 24 Therefore it is possible that moist wound healing in fact did have negative effect on healing.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly high levels of wound tissue hydration (hyper-hydration) have proved to be effective in aiding the healing process. A number of studies have indicated that a wound that is overly hydrated may not result in tissue damage (Breuing et al, 1992;Svensjö et al, 2000;Vranckx et al, 2002;Vogt et al, 1995), and rather suggest that a wound bathed in a hyper-hydrated environment may benefit from the advantages of moist wound healing (Junker et al, 2013).…”
Section: Hydration Assists Wound Healingmentioning
confidence: 99%